Enhancing Students' Scientific Skills Through a Low-Carbon Education-Based Youth Research Training Program - Warastuti, Renaning; Permana, Irvan; Suryani, Ai (Journal of Innovative Science Education, 2025)
The increasing consequences of global climate change underscore the necessity for the integration of low-carbon education and renewable energy frameworks within the educational paradigm for learners. This study develops a training curriculum for Youth Scientific Paper/Karya Ilmiah Remaja (KIR) that incorporates these principles to enhance students' scientific proficiency. Utilizing a Systematic Literature Review (SLR) approach, thirty indexed scholarly articles from the last decade were rigorously analyzed. The results reveal that the inclusion of low-carbon education and renewable energy within KIR training programs significantly improves students' abilities in critical thinking, problem-solving, and data analysis while concurrently fostering environmental awareness. Effective implementation strategies include project-based learning, hands-on renewable energy experiments (such as solar panels and wind turbines), and collaborations with environmental organizations. However, challenges such as limited resources, insufficient mentor training, and inadequate policy support hinder successful implementation. Despite these obstacles, the integration of low-carbon education and renewable energy within KIR initiatives holds substantial promise for cultivating environmentally responsible scientific skills among students. This initiative aligns with the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), SDG 7 (Affordable and Clean Energy), and SDG 13 (Climate Action), thus contributing to a more sustainable future.